Efektivitas edukasi tentang Covid-19 melalui aplikasi WhatsApp terhadap tingkat pengetahuan dan kepatuhan masyarakat melaksanakan protokol kesehatan di Kota Langsa - Zulkarnaini Zulkarnaini; Nora Hayani; Azwarni Azwarni (Politeknik Kesehatan Kemenkes Aceh, 2023)
Background: in 2021 the global world is still covered by the threat of Covid - 19 whose virus continues to mutate and is increasingly dangerous. Until now, the government is still trying to implement the program until the target is achieved. One of the things that can be tried to help the government's efforts to prevent and anticipate transmission is to provide education to change people's behavior.Objectives: the purpose of this research was to test the effectiveness of Covid-19 education using the online method through the Whatsapp application on the level of public knowledge and compliance in implementing health protocols in Langsa City.Methods: this study used a quasy experimental design, with a control group design, 100 respondents who were collected in public places in Langsa City, were included in two WhatsApp groups, 50 people each for the intervention group and the control group. Data collection using online questionnaires, July - August 2022, comprehensive education using videos and leaflets delivered repeatedly via Whatsapp, taking into account research ethics. Data analysis to test the effectiveness of using the paired sample T test by doing the previous normality and homogeneity tests.Results: the results of the study on the knowledge variable in the intervention group showed significant differences before and after the intervention, p-value 0.000 and t = 9.254. In the control group, there was no significant difference, p-value 0.125 and t -1.562. Variable compliance of respondents implementing health protocols, the group that was given the intervention, there was a significant difference, p-value 0.016 and t -2.488. In the control group, there was no difference with a p-value of 0.351 and t-0.942.Conclusion: online education through video media and leaflets given to the intervention group was effective in increasing respondents' knowledge, so that there was a significant difference in knowledge before and after providing education. Increased knowledge also increases respondents' compliance with health protocols